(untitled) (Verse Version, 2024)
“Rolling Thunder” is a poignant poem that employs rich metaphor and vivid imagery to explore themes of anxiety, human fragility, and mortality within a hospital setting. The poem juxtaposes the uncontrollable forces of nature—symbolized by thunder, wind, and rain—with the emotional and physical suffering of patients and their loved ones. Through striking comparisons, such as people waiting outside the ICU to ants sensing a storm, the poem conveys silent dread and helplessness. The hospital’s glass walls act as a “widescreen”, projecting the stark contrast between the indifferent outside world and the life-altering struggles within. The imagery of “frosted-glass lungs” and tears falling like rain underscores the visceral reality of illness, while the burden of medical payments adds another layer of distress. Structured in free verse, the poem’s fragmented flow mirrors the tension and uncertainty of hospital life. Ultimately, “Rolling Thunder” serves as a meditation on human vulnerability, the inevitability of suffering, and the isolating confrontation with mortality.